Sociolects and Registers – a Contrastive Analysis of Two Kinds of Linguistic Variation - Lewandowski, Marcin (Investigationes Linguisticae, 2010)
The paper, which is a theoretical contribution to investigations of social varieties of language, deals with two major dimensions of sociolinguistic variation: sociolectal and registerial. Drawing upon the views of Polish and Anglo-Saxon linguists, the author explores the concepts of sociolect (social dialect) and register, focusing mainly on their definitions, controlling variables, methodological frameworks, and typologies. In the final section, he attempts to shed some new light on the two kinds of variation and suggests new methodological solutions that could be applied in studies of sociolinguistic variation.